2014
DOI: 10.1111/are.12623
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fermented by-product of mushroom, Pleurotus ostreatus , as an additive on growth, serological characteristics and nonspecific immune responses in juvenile Amur catfish, Silurus asotus

Abstract: The present experiment was conducted to evaluate the efficacy of dietary fermented by-product of mushroom, Pleurotus ostreatus, (FBPM) as an additive in juvenile Amur catfish, Silurus asotus. Five diets were formulated to contain 0%, 0.1%, 0.2%, 0.4% and 0.8% (FBPM 0 , FBPM 0.1 , FBPM 0.2 , FBPM 0.4 and FBPM 0.8 respectively) of FBPM. Fifteen fish averaging 5.7 AE 0.1 g (Mean AE SD) were fed one of the five diets in triplicate groups at 3-4% of wet body weight/day for 8 weeks. Average weight gain (WG) and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 36 publications
(45 reference statements)
4
6
0
Order By: Relevance
“…Plasma TP was used as a fundamental indicator of physiological condition and health status of juvenile barramundi, in accordance with data reported for other species (Al‐Dohail, Hashim & Aliyu‐Paiko, ; Han et al., ; Katya, Yun, Yun, Lee & Bai, ; López, Flores‐Ibarra, Bañuelos‐Vargas, Galaviz & True, ; Sardar, Randhawa, Abid & Prabhakar, ). The TP level for fermented LM‐fed fish obtained in this study (43 g/L) was slightly higher than the reported TP concentration for barramundi when fed with narrowleaf lupin L .…”
Section: Discussionsupporting
confidence: 66%
“…Plasma TP was used as a fundamental indicator of physiological condition and health status of juvenile barramundi, in accordance with data reported for other species (Al‐Dohail, Hashim & Aliyu‐Paiko, ; Han et al., ; Katya, Yun, Yun, Lee & Bai, ; López, Flores‐Ibarra, Bañuelos‐Vargas, Galaviz & True, ; Sardar, Randhawa, Abid & Prabhakar, ). The TP level for fermented LM‐fed fish obtained in this study (43 g/L) was slightly higher than the reported TP concentration for barramundi when fed with narrowleaf lupin L .…”
Section: Discussionsupporting
confidence: 66%
“…The rainbow trout, just like other fish species in commercial aquaculture, is usually reared in enclosed spaces, and efforts have been made to increase productivity per unit space (Sakai ; Katya et al . ). This development has led to overcrowding, which tends to adversely affect the health of fish.…”
Section: Introductionmentioning
confidence: 97%
“…A massive expansion along with the intensification has led to sudden increase in the annual production of rainbow trout in the Republic of Korea and has reached 3066 ton in 2012 (FAO 2014). The rainbow trout, just like other fish species in commercial aquaculture, is usually reared in enclosed spaces, and efforts have been made to increase productivity per unit space (Sakai 1999;Katya et al 2014). This development has led to overcrowding, which tends to adversely affect the health of fish.…”
Section: Introductionmentioning
confidence: 99%
“…Its aquaculture production in 2018 was 10,530 metric tons valued at 306 million won taking account for 37.5% of total freshwater fish production in Republic of Korea (KOSTAT, ). Japanese eel, just like any other fish species in commercial aquaculture, is usually reared in enclosed spaces and efforts have been made to increase productivity per unit space (Bai, Katya, & Yun, ; Katya, Yun, Yun, Lee, & Bai, ). This development has led to overcrowding, which tends to adversely affect the immune system and become more susceptible to disease.…”
Section: Introductionmentioning
confidence: 99%